2000
DOI: 10.1007/s002590000260
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive grading of oligodendrogliomas: correlations between in vivo metabolic pattern and histopathology

Abstract: Several studies have shown that the prognosis of oligodendrogliomas is dependent on their histological grade. In order to identify a non-invasive method for the primary diagnosis and follow-up of these tumours, we investigated the relationship between their in vivo metabolism, assessed by positron emission tomography (PET), and their histological grade assessed at the same time. Forty-seven patients with histologically confirmed oligodendrogliomas were investigated. Conventional neuroradiological assessment by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
47
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(55 citation statements)
references
References 24 publications
7
47
1
Order By: Relevance
“…Thus, increased AMT uptake does not appear to be the consequence of tumor-induced seizures or interictal epileptiform activity during the tracer uptake. a-[ 11 C]methyl-L-tryptophan uptake in lowgrade tumors is of particular clinical interest because accurate delineation of recurrent or residual low-grade tumors is difficult on MRI and such tumors typically show low uptake on glucose and other amino-acid PET scans (DiChiro, 1987;Kaschten et al, 1998;Derlon et al, 2000;Benard et al, 2003). a-[ 11 C]methyl-L-tryptophan appears to be a unique PET tracer by showing increased uptake in DNETs, which do not accumulate several other PET tracers (Lee et al, 2000;Richardson et al, 2001;Maehara et al, 2004;Weckesser et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, increased AMT uptake does not appear to be the consequence of tumor-induced seizures or interictal epileptiform activity during the tracer uptake. a-[ 11 C]methyl-L-tryptophan uptake in lowgrade tumors is of particular clinical interest because accurate delineation of recurrent or residual low-grade tumors is difficult on MRI and such tumors typically show low uptake on glucose and other amino-acid PET scans (DiChiro, 1987;Kaschten et al, 1998;Derlon et al, 2000;Benard et al, 2003). a-[ 11 C]methyl-L-tryptophan appears to be a unique PET tracer by showing increased uptake in DNETs, which do not accumulate several other PET tracers (Lee et al, 2000;Richardson et al, 2001;Maehara et al, 2004;Weckesser et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…1 In PET studies metabolic differences have been demonstrated between low-grade and high-grade oligodendrogliomas. 36,37 In vivo MRS has already been shown to be useful in distinguishing the grades of other brain tumors (e.g. astrocytomas 11,14,[38][39][40] ).…”
Section: Resultsmentioning
confidence: 99%
“…PET scan may also be useful for grading ODG's non-invasively [7]. In a different study by Derlon et al demonstrated that anaplastic ODG's exhibited a higher 18F-flurodeoxy-glucose and methionine (MET) uptake than low grade ODG's [7].…”
Section: Discussionmentioning
confidence: 99%
“…Derlon et al in his study found that both these tumor types exhibit glucose hypo-metabolism but on methionine (MET) PET imaging, the uptake of MET was high in the oligo-dendroglioma lesions and decreased, normal or only moderately increased in the astrocytoma group [6]. PET scan may also be useful for grading ODG's non-invasively [7]. In a different study by Derlon et al demonstrated that anaplastic ODG's exhibited a higher 18F-flurodeoxy-glucose and methionine (MET) uptake than low grade ODG's [7].…”
Section: Discussionmentioning
confidence: 99%